The Relationship Between Service Quality And Customer Satisfaction At The Kawa Daun Biaro Hut - Andaresta, Ivo; Yulastri, Asmar (Universitas Negeri Padang, 2023)
This study aims to: 1) Describe the quality of service at Dangau Kawa Daun Biaro, 2) Describe customer satisfaction at Dangau Kawa Daun Biaro, and 3) Analyze whether there is a relationship between service quality and customer satisfaction at Dangau Kawa Daun Biaro. This type of research is classified into a correlational quantitative descriptive type. The population in this study were all customers of Dangau Kawa Daun Biaro, totaling 3,987 people. The research sample is 100 people with the sampling technique is non-probability sampling, using incidental sampling. Data collection techniques were carried out using a questionnaire (questionnaire) using a differential scale that has been tested for its validity and reliability. The results of this study are: 1) Service quality is in the good category (72%), with details of 14% indicating the very good category, 13% indicating the fairly good category, 1% indicating the not good category, and 0% indicating the very bad category good 2) Customer satisfaction is in the quite satisfied category (62%), with details of 33% indicating the category very satisfied, 5% indicating the category quite satisfied, 0% indicating the category not satisfied, and 0% indicating the category very dissatisfied